Faktor Prediksi yang Berhubungan dengan Tingkat Kelelahan pada Pasien Diabetes Melitus Tipe 2 - Handayani, Martuti Dwi; Rayasari, Fitrian; Fauziah, Munaya; Jumaiyah, Wati; Asmara, Amelia (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to prove self-management factors, self-efficacy, and PSIA conditions as a prediction of the level of fatigue of diabetes ellipse cross-station patients. The results showed a relationship between age (p = 0.0001) and the time it was diagnosed (p = 0.0005). HB1AC (P = 0,0005), Self Management (P = 0.0001), Self Efficacy (P = 0,0001), and Psychological Conditions (P = 0,0005). CONCLUSION: the level of fatigue in patients with type 2 diabetes mellitus in friendship hospitals is relatively highly influenced by age variables, long diagnoses, HB1AC, self-management, self-efficacy, and psychological conditions. Variables that affect are the value of HB1AC Diiiku with a variable psychological condition and other variables. Keywords: Type 2 Diabetes Mellitus, Level